Implementasi Program Buku Bergilir (BULIR) di Nagari Saok Laweh Kabupaten Solok - Vitria Suriyani, Ade; Khaidir, Afriva (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research is motivated by the lack of public interest in reading. This research was conducted using a qualitative approach with a descriptive method. The research location was carried out in Nagari Saok Laweh. In determining informants, researchers use purposive sampling methods and techniques. In this study using data types, namely primary data and secondary data. Data collection techniques are carried out by interviews, observation, and documentation. In testing the validity of the data, researchers used method triangulation techniques. As for data analysis techniques using data reduction, data presentation, and conclusions.  The results showed that the implementation of the Rotating Book Program (BULIR) in Nagari Saok laweh in Solok Regency was carried out in detail such as communication, disposition and bureaucratic structure. However, the implementation has not been carried out properly because the number of human resources is still small such as the number of cadres and the limited budget used.